"Doc, I Think My Meds Are Killing Me! Please Help…": Transdisciplinary Forces Unite to Refocus Pharmacotherapy for Older Adults. Issue 2 (7th December 2018) - Forman, Daniel E.; Zieman, Susan J.
Abstract : This Editorial comments on the Review Article bySchwartz et al . in this issue